Integration of Concrete Media and PhET Simulation in Fraction Learning Through Realistic Mathematics Approach in Elementary School - Latifah, Nur; Ressa, Ressa (Journal of Educational Sciences, 2025)
This study investigated the effectiveness of integrating concrete media and PhET simulation in fraction learning using a realistic mathematics approach in elementary schools. This study responded to students' difficulties in understanding abstract mathematical concepts, especially in adding and subtracting fractions with the same denominator. The method used was a quasi-experimental design with a non-equivalent control group design, involving 60 fourth-grade students divided into experimental and control groups. Pretest and posttest were given to both groups. Data were analyzed using paired and independent sample t-tests. The results showed a statistically significant increase in the learning outcomes of the experimental group. After the intervention, the experimental group achieved an average posttest score of 77.47 while the control group scored 40.30. The average difference between the two groups was 37.17 points, with a t value of 15.690 and a p value of 0.000 (p < 0.05). These findings confirm that the integration of concrete and digital media in fraction learning through a realistic mathematics approach significantly improves students' learning outcomes. This multimodal learning strategy effectively addresses common difficulties in fraction learning and offers a promising model for enhancing mathematics instruction at the elementary level.